EFFORTS TO IMPROVE TEACHERS' SKILLS IN MAKING POWER POINT LEARNING MEDIA THROUGH IN HOUSE TRAINING - Rusli Rusli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the condition that only few activities could be done during this online and long distance learning. As a result, many teachers were unable to make ICT-based learning media, especially power points. It was possible to conduct the training for making power point offline and online. For this reason, in-house training was believed to be helpful for teachers to improve their skills in making power points. This research was a classroom action research conducted at SDN 021 Pendekar Bahan from August to September 2020. The instruments were observation and interview sheets. The results of the study showed that the teachers’ skills in making power points increased. The data showed that the average score in cycle I was 60.85, and it increased to 75.42 in cycle II with good criteria. Based on the research results, it could be concluded that in-house training improved the teachers’ skills in making power point learning media.